THE POSSIBILITY OF GENERALIZED PROTEST AND SOCIAL EXPLOSION IN THE YEARS OF MAXIMUM SOLAR ACTIVITY - V. Souponitsky (Вестник университета, 2019)
The article has been devoted to the analysis and substantiation of the possibility of using the regularities of behavior of society and its individuals during the solar cycle, discovered by A. L. Chizhevsky, in the planning and implementation of social management. It has been proposed to exclude the negative development of events in our country during the 25th solar cycle to use the potential of the protest activity of society for the creation and development of the country, deploying the all-Russian program “Creation of modern ecological industry of Russia”, which requires the mobilization of efforts of the whole country and can create up to 10 million jobs for the youth.